Modification of Sporulation Medium for Isolation and Identification of Colletotrichum Gloeosporioiedes - A Causal Agent of Anthracnose of Mangifera Indica L - Alam, Ashraful; Adhikary, Sanjoy Kumar; Ahmed, Mahtalat (Global Journal Of Botanical Science, 2022)
In the present study, different isolates of Colletotrichum gloeosporioiedes were collected from different mango growing areas of Bangladesh. Pathogenecity was proved by using healthy excised leaves in laboratory conditions. Effects of mycelial growth and sporulation (formation of acervuli) on six different culture media were tested in vitro. The results revealed significant differences (p<0.05) mycelia growth among the media. The results also indicated that the mycelial growth was maximum in Potato Dextrose Agar (12.8mm) media and the lowest in Green Bean Agar (8.0mm). The study disclosed significant difference (p<0.05) of acervuli formation among the media. Among the 6 different media the maximum acervuli were produced in HLEA (4.0 per square. cm) medium. But the sporulating characters of the fungus were not produced well in PDA and HLEA media rather than OMA. Thus, to find out the best composition of OMA for further research was conducted to obtain better growth and acervuli production and sporulating characters. The results revealed significant difference (p<0.05) of different characters among the concentration of OMA, and 20g/L OMA produced significantly maximum setae, conidia and sticky masses of conidia than others. The study suggested that Oat Meal Agar (20g/L) composition was the best medium for the sporulation of C. gloeosporioiedes (Setae, conidia and sticky masses of spores).